Clinical impact of echocardiography-defined pulmonary hypertension on the clinical outcome in patients with multiple myeloma. Issue 43 (23rd October 2020) - Bae, SungA; Kim, Kye Hun; Yoon, Hyun Ju; Kim, Hyung Yoon; Park, Hyukjin; Cho, Jae Yeong; Kim, Min Chul; Kim, Yongcheol; Hong, Young Joon; Park, Hyung Wook; Kim, Ju Han; Ahn, Youngkeun; et al.
Abstract : Abstract: Pulmonary hypertension (PH) is a complication of multiple myeloma (MM); however, the clinical outcomes and prognosis are relatively not well known. We aimed to investigate the risk factors of transthoracic echocardiography-defined PH and its impact on the clinical outcome in patients with MM. A retrospective study was performed using data from the Chonnam National University Hwasun Hospital database for patients who underwent transthoracic echocardiography (TTE) within 1 month of the MM diagnosis between January 2007 and December 2017. PH was defined as an estimated right ventricular systolic pressure (RVSP) > 40 mmHg. A total of 390 patients were included. TTE-defined PH was observed in 107 patients (27%). During the follow-up period (median, 688 days), all-cause death was noted for 134 patients (34.4%). In the Kaplan-Meier survival analysis, the cumulative overall survival and cardiovascular death-free survival rates were significantly lower in the PH group than in the non-PH group ( P  < .001). In the propensity score-matched population, RVSP > 40 mmHg on TTE and history of congestive heart failure (CHF) were identified as the significant independent predictors of all-cause and cardiovascular death. This study reports that the prevalence of TTE-defined PH is higher in patients with MM than in the general population. Moreover, TTE-defined PH and a history of CHF are the independent prognostic factors for all-cause and cardiovascular death in patients with MM. These results highlight the risk of associated cardiovascular disease in patients with MM and emphasize the importance of management strategies that prevent the deterioration of cardiac function.